PHYTOCHEMICAL EVALUATION, STANDARDIZATION AND ANTIOXIDANT ACTIVITY OF Punica granatum AND Psidium guajava - P.R. Shirode; P.S.Wagh; P.T.Newadkar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
In current study, we accepted out a systematic record of the relative antioxidant activity in selected medicinal plant species extracts. The total ash value, loss on drying, water insoluble ash, acid insoluble ash, water extractive value and alcoholic extractive value was found to 5.37%, 5.08%, 1.394%, 3.98%, 9.94% and 4.76 respectively. 1, 1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging result of the extracts was determined spectrophotometrically. The maximum radical scavenging consequence was observed in ethyl acetate extract of Punica granatum with IC50 = 49.45 mg ml-1. The strength of radical scavenging power of Punica granatum extract was found to be 45 mg ml-1. better than synthetic antioxidant butylated hydroxy toluene (BHT). The superior amount of phytoconstituent compounds leads to further potent radical scavenging result as shown by Punica granatum leaves extract.